2017
DOI: 10.5194/acp-17-11227-2017
|View full text |Cite
|
Sign up to set email alerts
|

Comparative measurements of ambient atmospheric concentrations of ice nucleating particles using multiple immersion freezing methods and a continuous flow diffusion chamber

Abstract: Abstract. A number of new measurement methods for ice nucleating particles (INPs) have been introduced in recent years, and it is important to address how these methods compare. Laboratory comparisons of instruments sampling major INP types are common, but few comparisons have occurred for ambient aerosol measurements exploring the utility, consistency and complementarity of different methods to cover the large dynamic range of INP concentrations that exists in the atmosphere. In this study, we assess the comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
72
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 42 publications
11
72
1
Order By: Relevance
“…However, again, there was considerable scatter in the data, especially for the CFDC measurements, indicating that changes in measured n INP were driven by variability in overall concentration, and not just processing temperature during this study. As with previous studies (DeMott et al, ), we also observed good agreement, in general, between n INP measured by the CFDC and the IS, with the respective cloud of values falling on top of each other in the region of overlapping temperatures. Figure also shows the CFDC data measured from the G‐1 during the CalWater 2011 campaign, hereafter CalWater‐1 (blue circles).…”
Section: Resultssupporting
confidence: 91%
“…However, again, there was considerable scatter in the data, especially for the CFDC measurements, indicating that changes in measured n INP were driven by variability in overall concentration, and not just processing temperature during this study. As with previous studies (DeMott et al, ), we also observed good agreement, in general, between n INP measured by the CFDC and the IS, with the respective cloud of values falling on top of each other in the region of overlapping temperatures. Figure also shows the CFDC data measured from the G‐1 during the CalWater 2011 campaign, hereafter CalWater‐1 (blue circles).…”
Section: Resultssupporting
confidence: 91%
“…The variability was not systematic, that is, showing one technique always being lower than another technique. A similar conclusion was reached by DeMott et al () for an intercomparison using ambient aerosol. This suggests that the precision of cold‐stage derived INP concentration is not better than 1 order of magnitude.…”
Section: Resultssupporting
confidence: 85%
“…also includes n INPs measured by the HINC-EV (ALL) and DFPC (CLEAN sector only). HINC-EV measurements of n INPs, À30°C fall within an order of magnitude of n INPs estimated from an extrapolation of the IS INP spectra to colder temperatures(Figure 4a), indicating good method agreement based on recent comparisons between ice nucleation measurement techniques(DeMott et al, 2017). At À22°C in the CLEAN sector, the…”
supporting
confidence: 72%